Tuning magnetostructural phase transition in CoMn0.88Cu0.12Ge by application of hydrostatic pressure. (September 2022) - Deptuch, Aleksandra; Duraj, Ryszard; Szytuła, Andrzej; Penc, Bogusław; Juszyńska-Gała̧zka, Ewa; Baran, Stanisław
Graphical abstract: Abstract: Structural and magnetic properties of CoMn0.88 Cu0.12 Ge have been investigated using X-ray diffraction and differential scanning calorimetry (DSC) accompanied with investigation of magnetic properties under applied hydrostatic pressure up to 12 kbar. The orthorhombic crystal structure (TiNiSi-type), which is dominant at low temperatures, turns into the hexagonal one (Ni 2 In-type), slightly above 200 K. The structural transition is of the first-order type as confirmed by presence of distinct thermal hysteresis. The ac magnetic measurements indicate a ferromagnetic order below 238 K, followed by additional anomaly at lower temperatures – the latter one being related to the structural transition. Application of hydrostatic pressure leads to temperature separation of the purely magnetic transition, whose Curie temperature increases with applied pressure, and the magnetostructural transition characterized by decreasing critical temperature. Comparison of the DSC data for the investigated compound and the isostructural CoMn0.95 Cu0.05 Ge has made it possible to determine both the structural and magnetic components of entropy change.